2018
DOI: 10.1007/s12602-018-9405-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synbiotic Supplementation on Metabolic Status in Women With Polycystic Ovary Syndrome: a Randomized Double-Blind Clinical Trial

Abstract: www.irct.ir : IRCT201604015623N71.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
0
35
0
3
Order By: Relevance
“…53 Interestingly, administration of a synbiotic formula to women suffering from polycystic ovary syndrome for 12 weeks resulted in decreased levels of plasma glucose, triglyceride, and cholesterol levels. 62 Importantly, it was previously found that certain Lactobacillus strains isolated from human breast milk could combat cervical cancer via inducing apoptosis and inhibiting proliferation. 63 In particular, L. casei potentiated the antiproliferative effect of geniposide through the production of b-glucosidase in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…53 Interestingly, administration of a synbiotic formula to women suffering from polycystic ovary syndrome for 12 weeks resulted in decreased levels of plasma glucose, triglyceride, and cholesterol levels. 62 Importantly, it was previously found that certain Lactobacillus strains isolated from human breast milk could combat cervical cancer via inducing apoptosis and inhibiting proliferation. 63 In particular, L. casei potentiated the antiproliferative effect of geniposide through the production of b-glucosidase in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…bulgaricus , S. thermophilus , L. paracasei ssp . paracasei (2.4×10 9 CFU per day) 113 Adults with T1DM and T2DM on haemodialysis, n = 60 Inulin (0.8 g per day) L. acidophilus , L. casei , B. bifidum (2×10 9 CFU of each per day) 114 Treatment of irritable bowel syndrome Adults, n = 85 FOS (100 mg, three times per day) Bacillus coagulans (15×10 7 spores, three times per day) 115 Children, n = 71 Inulin (900 mg, twice per day) B. lactis B94 (5×10 9 CFU, twice per day) 116 Eradication of Helicobacter pylori Adults, n = 76 FOS (250 mg per day) L. casei PXN 37, L. rhamnosus PXN 54, S. thermophilus PXN 66, B. breve PXN 25, L. acidophilus PXN 35, B. longum PXN 30, L. bulgaricus PXN 39 (2×10 8 CFU per day) 117 Children and youth, n = 104 Inulin (900 mg per day) B. lactis B94 (5×10 9 CFU per day) 118 Treatment of polycystic ovarian syndrome Adults, n = 60 Inulin (800 mg per day) L. acidophilus strain T16 (IBRC-M10785), L. casei strain T2 (IBRC-M10783), B. bifidum strain T1 (IBRC-M10771) (2×10 9 CFU/g of each per day) 119 Adults, n = 60 Inulin (800 mg per day) L. acidophilus strain T16 (IBRC-M10785), L. casei strain T2 (IBRC-M10783), B. bifidum strain T1 (IBRC-M10771) (2×10 9 CFU/g of each per day) 120 Treatment of chronic kidney disease Adults, n = 30 Inulin (2.2 g), tapioca-resistant starch (1.3 g) (three times per day) L. plantarum (5×10 9 ), L. casei subsp. r hamnosus (2×10 9 ), Lactobacillus gasseri (2×10 ...…”
Section: Current Levels Of Evidencementioning
confidence: 99%
“…Patients were examined by the otolaryngologist at the clinic and diagnosed with chronic sinusitis based on clinical observations and CT scan findings. After obtaining written consent, patients were randomly assigned to three groups using a randomized block table [13][14][15][16][17]. Patients in the first group received dexmedetomidine infusion at a dose of 2. μg/kg Patients in the second group received dexmedetomidine infusion at a dose of 0.5. μg/kg patients in the third group receive normal saline as a placebo.…”
Section: Methodsmentioning
confidence: 99%